Formulation development and in vitro evaluation of nanosuspensions loaded with Atorvastatin calcium - N, Arunkumar; M, Deecaraman; C, Rani; K P, Mohanraj; K, Venkateskumar (Asian Journal of Pharmaceutics (AJP), 2014)
The aim of this study was to prepare and characterize nanosuspensions of a poorly soluble drug (Atorvastatin calcium) in order to enhance its solubility and dissolution characteristics. Nanosuspensions were prepared by high pressure homogenization technique.They were characterized by thermal gravimetric analysis (TGA), differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), solubility, and in vitro drug release studies. The absence of atorvastatin peaks in PXRD profiles of nanosuspensions suggests the transformation of crystalline drug into an amorphous form.TGA examination suggested that the drug was converted into anhydrous form from the original trihydrate form. DSC curves also compliment the result obtained by TGA and PXRD. The effect of particle size was found to be significant on the saturation solubility of the drug.The in vitro drug release studies showed a significant increase in the dissolution rate of nanosuspensions as compared with pure drug. This study has shown that initial crystalline state is reduced following particle size reduction and that the dissolution characteristics of atorvastatin nanosuspensions were significantly increased in regards to the pure drug.The method being simple and easily scaled up, this approach should have a general applicability to many poorly water-soluble drug entities.